Social representations of scholarships in a situation of vulner- ability by the university community. The case of Peru (2014-2020) - Menendez Condor, Pamela Fabiola (Mediaciones Sociales, 2021)
The Beca 18 Program is a national program in Peru that, to date, has benefited 70,921 young people with low economic resources or situations of vulnerability. The objective of this study is to analyze the social representations of the academic community of the Universidad Peruana Cayetano Heredia (Lima headquarters) towards the scholarship holders of the Beca 18 Program. In this research work, in-depth interviews were carried out, the main result of which was that the representations by the academic community influence the insertion and adaptation of the scholarship holders. Likewise, this study focuses on scholarship holders from rural regions, as they are the ones who have the greatest obstacles to inserting themselves and adapting to university life
Keywords: representations; accademic community; scholarship program 18; peruvian scholars